Vaccination ethics - Giubilini, A (Oxford University Press, 2020)
Introduction or background Vaccination decisions and policies present tensions between individual rights and the moral duty to contribute to harm prevention. This article focuses on ethical issues around vaccination behaviour and policies. It will not cover ethical issues around vaccination research. Sources of data Literature on ethics of vaccination decisions and policies. Areas of agreement Individuals have a moral responsibility to vaccinate, at least against certain infectious diseases in certain circumstances. Areas of controversy Some argue that non-coercive measures are ethically preferable unless there are situations of emergency. Others hold that coercive measures are ethically justified even in absence of emergencies. Growing points Conscientious objection to vaccination is becoming a major area of discussion Areas timely for developing research The relationship between individual, collective and institutional responsibilities to contribute to the public good of herd immunity will be a major point of discussion, particularly with regard to the COVID-19 vaccine.